Study of various adsorbent-refrigerant pairs for the application of solar driven adsorption cooling in tropical climates - Habib, K. (Elsevier Ltd, 2014)
This article presents analytical investigation results on the performance of solar powered adsorption cooling systems for Malaysia and similar tropical regions. The studied adsorbent-refrigerant pairs are silica gel-water, activated carbon fiber-ethanol and activated carbon-methanol. A computer simulation program has been developed for modeling and performance evaluation for the solar driven adsorption cooling cycle using the meteorological data of Kuala Lumpur, Malaysia The simulation is based on the experimentally confirmed adsorption isotherms, kinetics and isosteric heat of the adsorption data for the respective adsorbent-refrigerant pairs. The optimum cooling capacity and coefficient of performance (COP) of the different adsorbent-refrigerant pairs varying adsorption-desorption cycle time, regeneration temperature and chilled water inlet temperature are calculated and compared. Â© 2014 Elsevier Ltd. All rights reserved.